Fracture of a narrow-diameter roxolid implant: clinical and fractographic considerations - Karl, Matthias; Krafft, Tim; Kelly, J. Robert (International Journal of Oral & Maxillofacial Implants, 2014)
Narrow-diameter implants have become popular, as bone augmentation procedures can frequently be avoided. In order to provide implants with sufficient strength, a titanium-zirconium (Ti-Zr) alloy has recently been introduced purportedly showing improved mechanical properties as compared to commercially pure titanium (cpTi). This paper reports on the clinical and fractographic aspects of a fractured Ti-Zr implant, generally considered a rare event.A narrow-diameter Ti-Zr implant was placed in a patient aged 66 years in the area of the maxillary right canine and used to support a removable partial denture retained by cylindrical telescopic crowns placed on the implant and on the maxillary left canine. Eleven months after successful osseointegration, the patient presented with a horizontally fractured implant. The fractured part was retrieved for fractographic analysis.The implant fractured just apical to the abutment screw, where the wall thickness of the implant is minimal. Scanning electron microscopy (SEM) analysis revealed the starting point of the fracture at the palatal aspect of the implant. No fatigue striations could be observed, indicating a brittle fracture atypical for Ti-based alloys.The fractographic observations correlate with the given loading situation, which is characterized by high levels of moment loading being imposed on the implant by a rigidly retained cantilever prosthesis. Mechanical overload going beyond the approved indications for Roxolid implants (Straumann) has to be seen as primary cause for this fracture.
EVALuna2:24817

Outcome of bonded vs all-ceramic and metal- ceramic fixed prostheses for single tooth replacement - Karl, Matthias (European Journal of Oral Implantology, 2016)
The conventional treatment of a single missing tooth is most frequently based on the provision of a fixed dental prosthesis (FDPs). A variety of designs and restorative materials are available which have an impact on the treatment outcome. Consequently, it was the aim of this review to compare resin-bonded, all-ceramic and metal-ceramic FDPs based on existing evidence.An electronic literature search using "metal-ceramic" AND "fixed dental prosthesis" AND "clinical, all-ceramic" AND "fixed dental prosthesis" AND "clinical, resin-bonded" AND "fixed dental prosthesis" AND "clinical, fiber reinforced composite" AND "clinical, monolithic" AND "zirconia" AND "clinical" was conducted and supplemented by the manual searching of bibliographies from articles already included.A total of 258 relevant articles were identified. Metal-ceramic FDPs still show the highest survival rates of all tooth-supported restorations. Depending on the ceramic system used, all-ceramic restorations may reach comparable survival rates while the technical complications, i.e. chipping fractures of veneering materials in particular, are more frequent. Resin-bonded FDPs can be seen as long-term provisional restorations with the survival rate being higher in anterior locations and when a cantilever design is applied. Inlay-retained FDPs and the use of fiber-reinforced composites overall results in a compromised long-term prognosis. Recently advocated monolithic zirconia restorations bear the risk of low temperature degradation.Several variables affect treatment planning for a given patient situation, with survival and success rates of different restorative options representing only one factor. The broad variety of designs and materials available for conventional tooth-supported restorations should still be considered as a viable treatment option for single tooth replacement.
EVALuna2:24826

Parameters determining micromotion at the implant-abutment interface - Karl, Matthias; Taylor, Thomas D. (International Journal of Oral & Maxillofacial Implants, 2014)
Micromotion at the implant-abutment level has been reported to be a major determinant of longterm implant success, as technical problems ranging from screw loosening to screw fracture may occur as a consequence of excessive micromotion.Following published standards, implant-abutment assemblies were fixed in a universal testing machine at a 30-degree angle. A cyclic load of 200 N was applied to the specimens 10 times at a crosshead speed of 100 N/s while relative displacement between the implant and the abutment was quantified using extensometers. For five consecutive loading cycles per specimen, micromotion was recorded as a basis for statistical analysis, with two-sample t tests (Welch test) applied.Micromotion at the implant-abutment interface ranged from 1.52 to 94.00 ?m. While a significant effect of tightening torque was found, implant shoulder design did not reveal a significant effect in all cases. Lack of engagement of antirotational features of the implants resulted in increased micromotion. Casting onto prefabricated gold cylinders resulted in abutments with significantly less micromotion as compared to copy-milled and stock abutments. Computer-aided design/computer-assisted manufacture (CAD/CAM) zirconia abutments showed less micromotion than CAD/CAM titanium abutments. Inconsistent levels of micromotion were recorded for CAD/CAM abutments coupled to proprietary and competing implant systems. Great variations in micromotion were found with clone abutments and clone implant systems.A broad range of micromotion values was observed with the implant abutment combinations investigated. There seems to be no perfect implant shoulder geometry or perfect fabrication technique that would result in no detectable micromotion.
EVALuna2:24818